A stable high-performance isotropic electrorheological elastomer towards controllable and reversible circular motion. (15th July 2020) - Yuan, Xin; Zhou, Xuefeng; Liang, Yudai; Wang, Lijuan; Chen, Riming; Zhang, Mengying; Pu, Huayan; Xuan, Shouhu; Wu, Jinbo; Wen, Weijia
Abstract: In this paper, two kinds of isotropic giant electrorheological elastomers (GERE) were prepared with urea-coated barium titanyl oxalate nanoparticles as dielectric particles filler, poly (dimethyl siloxane) (PDMS) as an elastic matrix and silicone oil as a plasticizer. Such GEREs are far superior to other isotropic and even anisotropic electrorheological elastomers (EREs), showing excellent electrorheological (ER) performance. The theoretic mechanism in elastomers prepared by us should be explained by saturation surface polarization or orientational polarization model. More interestingly, the storage modulus increment (ΔG′) of GEREs displays curvilinear dependence on the electric field due to poor particle mobility and different mobility under different electric fields, rather than a predicted linear variation. After testing their viscoelastic and dielectric properties and microstructures, we found that too high of the powder content leads to the serious agglomeration of particles and the performance degradation of the elastomer. An incorporation of silicone oil improved the dispersion state and wettability between the particles and matrix. At the same time, silicone oil reduced the hardness of the matrix and made the particles align more easily in the PDMS matrix. Lower initial modulus and higher field-induced modulus make GEREs containing silicone oil have ultrahigh storage modulus sensitivity, in which the best-performing sample achieved a storage modulus change exceeding 400 kPa and attained a maximum relative ER effect of 3280% at 3 kV/mm. Finally, the GERE was used to reversibly control the amplitude of circular motion within seconds by varying electric fields, revealing broad potential application in vibration control. Graphical abstract: Image 1 Highlights: The nano-filler content on isotropic giant electrorheological elastomers is optimized. The effects of silicone oil plasticizer on giant electrorheological elastomers is studied. The highest storage module and relative ER effect achieved 421 kPa and 32.8. The field-induced modulus remained almost unchanged after 45 days. Circular motion amplitudes could be tuned reversibly from 10.6 mm to 8.8 mm within seconds.